Association of Sedentary Time with Mortality Independent of Moderate to Vigorous Physical Activity - Koster, Annemarie; Caserotti, Paolo; Patel, Kushang V.; Matthews, Charles E.; Berrigan, David; Van Domelen, Dane R.; Brychta, Robert J.; Chen, Kong Y.; Harris, Tamara B. (PloS one, 2012)
Sedentary behavior has emerged as a novel health risk factor independent of moderate to vigorous physical activity (MVPA). Previous studies have shown self-reported sedentary time to be associated with mortality; however, no studies have investigated the effect of objectively measured sedentary time on mortality independent of MVPA. The objective our study was to examine the association between objectively measured sedentary time and all-cause mortality. 7-day accelerometry data of 1906 participants aged 50 and over from the U.S. nationally representative National Health and Nutrition Examination Survey (NHANES) 2003-2004 were analyzed. All-cause mortality was assessed from the date of examination through December 31, 2006. Over an average follow-up of 2.8 years, there were 145 deaths reported. In a model adjusted for sociodemographic factors, lifestyle factors, multiple morbidities, mobility limitation, and MVPA, participants in third quartile (hazard ratio (HR):4.05; 95%CI:1.55-10.60) and fourth quartile (HR:5.94; 95%CI: 2.49-14.15) of having higher percent sedentary time had a significantly increased risk of death compared to those in the lowest quartile. Our study suggests that sedentary behavior is a risk factor for mortality independent of MVPA. Further investigation, including studies with longer follow-up, is needed to address the health consequences of sedentary behavior.